2012
DOI: 10.1097/hjh.0b013e32835726c1
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced mitochondrial reactive oxygen species and peroxiredoxin-3 expression in cardiac fibroblasts

Abstract: Our data indicate that ANG II-stimulated mitochondrial reactive oxygen species production in rat cardiac fibroblasts is accompanied by a reduction in the expression of the mitochondrial antioxidant Prx-3, and thereby potentially contributing to oxidative stress in the myocard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In the present study, TRPM7 expression was increased in SAN tissues in SSS rats together with a significant increase in Smad2 phosphorylation level, suggesting the involvement of TRPM7/Smad2 in Ang II-mediated myocardial fibrosis. Many clinical studies have demonstrated that Ang II contributes to the cardiac remodeling that occurs in hypertensive heart disease, heart failure, myocardial infarction, cardiomyopathy, and paroxysmal atrial fibrillation with sick sinus syndrome [ 35 38 ]. In addition, Ang II expression is more pronounced in myocardial tissue with elevated cardiac load due to fibrosis than in normal myocardial tissues and is closely related to interstitial fibrosis in myocardium [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, TRPM7 expression was increased in SAN tissues in SSS rats together with a significant increase in Smad2 phosphorylation level, suggesting the involvement of TRPM7/Smad2 in Ang II-mediated myocardial fibrosis. Many clinical studies have demonstrated that Ang II contributes to the cardiac remodeling that occurs in hypertensive heart disease, heart failure, myocardial infarction, cardiomyopathy, and paroxysmal atrial fibrillation with sick sinus syndrome [ 35 38 ]. In addition, Ang II expression is more pronounced in myocardial tissue with elevated cardiac load due to fibrosis than in normal myocardial tissues and is closely related to interstitial fibrosis in myocardium [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the subcellular level, Prdx1 and Prdx2 were found throughout the cell, while Prdx3 and Prdx5 were primarily mitochondrial, some nuclear labeling was observed. Recent studies point to the importance of Prdxs to exert protective antioxidant effects in various cells [ 28 , 29 ]. However, the physiological effects and the underlying mechanisms of Prdxs in renal fibrosis have not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The rennin-angiotensin system plays a central role in cardiac structural remodeling and in the development of myocardial fibrosis in several disease states including CHF [47], myocardial infarction [48], and cardiomyopathy [49]. ROS production is elevated by AngII and hypertension [50, 51]. In response to hypoxia, fibroblasts differentiate to myofibroblasts [52], thereby initiating the fibrotic process.…”
Section: Signaling Pathways Involved In Cardiac Fibrosismentioning
confidence: 99%